2016
DOI: 10.1007/s11886-016-0700-6
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control and Excess Cardiovascular Mortality in Type 1 Diabetes

Abstract: Diabetes mellitus is a chronic systemic disease with multiple complications ranging from microvascular to macrovascular diseases. Type 1 diabetes comprises 5 % of adults with diabetes in the US. This population is shown to be at increased risk of cardiovascular events and mortality. Intensive glycemic control has been consistently associated with decreased microvascular complications but trials on macrovascular benefit yielded mixed results over the years. Recent data from long-term observational follow-up stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, it should be noted that, in our study individuals with any given complication could have subclinical levels of other complications. Other studies have found an association between proliferative retinopathy and mortality risk [29,30]. An even stricter definition of retinopathy might have enabled us to support these findings; however, such detailed information was not available in the dataset at hand.…”
Section: Discussionmentioning
confidence: 73%
“…However, it should be noted that, in our study individuals with any given complication could have subclinical levels of other complications. Other studies have found an association between proliferative retinopathy and mortality risk [29,30]. An even stricter definition of retinopathy might have enabled us to support these findings; however, such detailed information was not available in the dataset at hand.…”
Section: Discussionmentioning
confidence: 73%
“…However, the fact that the hypertrophic cardiomyopathy and left ventricular dysfunction in a mouse model of lipodystrophy were ameliorated by lowering blood glucose levels (11) suggests hyperglycemia may contribute to impaired cardiac function in diabetes. Furthermore, nonobese patients with diabetes (including type 1 or monogenic diabetes) may also develop cardiac complications (12,13), supporting the idea that hyperglycemia alone is sufficient to cause cardiac disease. Likewise, in a large study of individuals with type 2 diabetes (T2D), a 1% increase in HbA 1c was associated with an increased risk of heart failure, independent of obesity, suggesting hyperglycemia is an independent risk factor for cardiac dysfunction (14).…”
mentioning
confidence: 87%